Harnessing Mechanisms of Immune Tolerance to Improve Outcomes in Solid Organ Transplantation: A Review - Slepicka, Priscila Ferreira; Yazdanifar, Mahboubeh; Bertaina, Alice (Frontiers in Immunology, 2021)
Survival after solid organ transplantation (SOT) is limited by chronic rejection as well as the need for lifelong immunosuppression and its associated toxicities. Several preclinical and clinical studies have tested methods designed to induce transplantation tolerance without lifelong immune suppression. The limited success of these strategies has led to the development of clinical protocols that combine SOT with other approaches, such as allogeneic hematopoietic stem cell transplantation (HSCT). HSCT prior to SOT facilitates engraftment of donor cells that can drive immune tolerance. Recent innovations in graft manipulation strategies and post-HSCT immune therapy provide further advances in promoting tolerance and improving clinical outcomes. In this review, we discuss conventional and unconventional immunological mechanisms underlying the development of immune tolerance in SOT recipients and how they can inform clinical advances. Specifically, we review the most recent mechanistic studies elucidating which immune regulatory cells dampen cytotoxic immune reactivity while fostering a tolerogenic environment. We further discuss how this understanding of regulatory cells can shape graft engineering and other therapeutic strategies to improve long-term outcomes for patients receiving HSCT and SOT.